JOYCE BETWEEN AUSCHWITZ AND SIBERIA, OR A ZONING OF TOTALITARIANISM - Jukić, Tatjana (2011)
Taking up the sustained surfacing of Joyce in Danilo Kiš's fiction and criticism, my presentation will address the specific position of Joyce in Kiš's various and obsessive representations of the concentration camp experience. I argue that Joyce cuts a narrative figure in Kiš where a zoning of totalitarianism becomes possible, even necessary ; that Joyce in Kiš demands that generalizing approaches to totalitarianism be dismantled in favor of discrete political configurations irreducible to the totalizing of political experience.